Pengaruh pendapatan nelayan terhadap gaya hidup masyarakat di Desa Pemangkat Kota Kecamatan Pemangkat - Muslimah, Muslimah; Agam, Beryaldi; Martin, Riki (Universitas Halu Oleo, 2023)
This study is intended to obtain an explanation of the relationship between the influence of fishermen's income on the lifestyle of the community in Pemangkat Kota Village, Pemangkat District. Where the welfare of the fishing community in Pemangkat Kota Village, Pemangkat District is not achieved by external and internal factors and lack of attention from the local government. This study used a questionnaire with 53 respondents. This is evidenced by the results obtained based on the results of hypothesis testing. This significant effect can be seen based on the results of the t test on the independent variable/management information system obtained a Sig value of 0.000. A probability value greater than the Sig value (0.05 > 0.000). In addition to using the Sig value, to see the significance of the effect of fishermen's income on people's lifestyles, they can also compare T tables with T test. The result of the coefficient shows the value of T test X1 (5.415). while for T tabel with a significant level of 5% obtained a value of T51: 0.025 = 2.00758 (seen in T tabel with a free degree of 51 and a significant level = 0.025). The comparison of the two yields T test > T tabel, namely T test (5.415) > T tabel (2.00758). The results of the comparison of the two can be concluded that the value of T test > T tabel then Ha is accepted and Ho is rejected, so that the income variable (X1) affects the lifestyle of people in Pemangkat Kota Village, Pemangkat.